Eine prophetische Gruppe in Zion und ein priesterlicher Übersetzer in der Diaspora: zur Deutung der Sprecheridentität in Jes 61 MT und Jes 61 LXX - Spans, Andrea (Biblische Notizen, 2012)
Considering where the material in Isa 61 MT comes from and how it is creatively re-used, there is evidence to assume that Isa 61 MT contains the vision of a prophetic group in postexilic Jerusalem. This group is committed to social affairs and vehemently distances itself from the official priesthood by wanting the poor to be released and actually to be the new priests. In contrast, the priestly translator in Isa 61 LXX reflects upon the situation outside the land: By translating Hebrew keywords differently or by establishing new Greek keywords he conveys a strong message of hope to return from the diaspora to Jerusalem.